2013
DOI: 10.1002/anie.201306231
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Hydrogenation of α‐Acyloxy‐1‐arylethanones

Abstract: First hand: The first example of a palladium-catalyzed asymmetric hydrogenation of α-acyloxy ketones (1) was accomplished to give the hydrogenated products 2 with by far the highest catalytic efficiency in up to quantitative conversions and excellent enantioselectivities. The hydrogenated products could serve as important intermediates for the preparation of many drug candidates. TFE=2,2,2-trifluoroethanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 105 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Still further, the catalytic system was successfully applied to α‐acyloxy, α‐morpholino and α‐semialdehyde ketones ( 3 m – 3 p ; Table 3, entries 13–16), with the α‐functional groups tolerated and high yields obtained for all of the desired products. Selective reduction of analogues of 3 m by TH is difficult, because the acyl group is prone to migration by hydrolysis 17. Indeed, there are only a few literature reports describing the TH of this class of substrates; however, the catalyst loadings are high and the yields are relatively low due to the aforementioned problem 18.…”
Section: Resultsmentioning
confidence: 99%
“…Still further, the catalytic system was successfully applied to α‐acyloxy, α‐morpholino and α‐semialdehyde ketones ( 3 m – 3 p ; Table 3, entries 13–16), with the α‐functional groups tolerated and high yields obtained for all of the desired products. Selective reduction of analogues of 3 m by TH is difficult, because the acyl group is prone to migration by hydrolysis 17. Indeed, there are only a few literature reports describing the TH of this class of substrates; however, the catalyst loadings are high and the yields are relatively low due to the aforementioned problem 18.…”
Section: Resultsmentioning
confidence: 99%
“…Saturated Na 2 CO 3 was added, the mixture was extracted with ethyl acetate, and the extracts were washed with brine, dried over MgSO 4 , filtered, and concentrated. The residue was purified by chromatography to give target compounds 15a-d. 32,33) CDI (10.0 mmol) was dissolved in N,N-dimethylformamide (DMF) (20 mL) and to this solution a solution of the carboxylic acids 14a and d (10.0 mmol) in DMF (2 mL) was added dropwise. Subsequently, the reaction mixture was stirred at room temperature for 1 h. Then, H 2 S was bubbled gently through the reaction mixture for 2 h. Sulfuric acid (0.5 M, 40 mL) was added and the mixture was extracted with ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…[6] During studies on these reactions,as mall amount of aC À Ob ond-cleavage product was observed. [6] During studies on these reactions,as mall amount of aC À Ob ond-cleavage product was observed.…”
mentioning
confidence: 99%
“…This unexpected discovery inspired the current research utilizing palladium-catalyzed hydrogenolysis for the chemo-and enantioselective CÀOb ond cleavage of ester alkyl side-chains. [6] Thes ubstrate scope of the catalytic system was explored using the optimized reaction conditions (Schemes 2a nd 3). Only the hydrogenated product 3a was obtained in TFE and DCM with full conversion (entries 1and 2), and almost no reaction occurred Scheme 1.…”
mentioning
confidence: 99%